2022
DOI: 10.1111/anae.15671
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced peri‐operative care to improve outcomes for high‐risk surgical patients in Brazil: a single‐centre before‐and‐after cohort study

Abstract: Summary Mortality and morbidity for high‐risk surgical patients are often high, especially in low‐resource settings. Enhanced peri‐operative care has the potential to reduce preventable deaths but must be designed to meet local needs. This before‐and‐after cohort study aimed to assess the effectiveness of a postoperative 48‐hour enhanced care pathway for high‐risk surgical patients (‘high‐risk surgical bundle’) who did not meet the criteria for elective admission to intensive care. The pathway comprised of six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…We have already shown that adequate surgical ward teams improve patient safety and can reduce the incidence of postoperative complications and mortality. 11 Therefore, in hospitals that provide excellent ward-based care, the incremental benefit of ICU admissions for stable patients will be reduced. 27…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have already shown that adequate surgical ward teams improve patient safety and can reduce the incidence of postoperative complications and mortality. 11 Therefore, in hospitals that provide excellent ward-based care, the incremental benefit of ICU admissions for stable patients will be reduced. 27…”
Section: Discussionmentioning
confidence: 99%
“…In response to these challenges, we developed the Ex-Care risk model to identify high-risk surgical patients, 8 categorizing them as high-risk (5–10% likelihood of death) or very high-risk (>10% probability of death). A care bundle for these patients was successfully implemented in surgical wards, 11 with a particular interest in the outcomes of high-risk patients electively admitted to ICU.…”
Section: Introductionmentioning
confidence: 99%
“…To be considered complete, a quality improvement project must involve two phases of outcome assessmentone before and one after an interventionevaluating the same metrics, using the same instruments (which should be designed and thoroughly piloted before the first attempt at assessment is made) and should be as rigorous as a before-and-after clinical trial. Authors should also consult already published exemplars of quality science to inform their own research, keeping in mind the difference between quality assurance and audit, and quality improvement projects [4,[13][14][15].…”
Section: Good Quality Science Projects Should Deliver Insightsmentioning
confidence: 99%
“…This postoperative enhanced care pathway for high-risk surgical patients, or in other words, a “high-risk surgical bundle” with a patient-centered decision-making, may significantly improve the patient's experience and outcomes through the surgical process for patients at higher risk of adverse events. 24 In this context, a recent before-and-after cohort study with a clinical pathway based on enhanced surveillance for high-risk surgical patients has demonstrated a significant reduction of in-hospital mortality. 24 Particularly in this study, the “high-risk surgical bundle” has included six main elements, such as risk identification and communication, adoption of a high-risk post anesthesia care unit discharge checklist, prompt nursing admission to ward, intensification of vital signs monitoring, perioperative troponin measurement, and prompt access to medical support if required.…”
mentioning
confidence: 99%
“… 24 In this context, a recent before-and-after cohort study with a clinical pathway based on enhanced surveillance for high-risk surgical patients has demonstrated a significant reduction of in-hospital mortality. 24 Particularly in this study, the “high-risk surgical bundle” has included six main elements, such as risk identification and communication, adoption of a high-risk post anesthesia care unit discharge checklist, prompt nursing admission to ward, intensification of vital signs monitoring, perioperative troponin measurement, and prompt access to medical support if required. 24 New research is still warranted to further evaluate which strategies designed to enhance perioperative care can actually reduce morbidity and mortality in high-risk surgical subpopulations.…”
mentioning
confidence: 99%